Another new micro-endemic, limestone-dwelling leaf-toed gecko (Gekkonidae: Dixonius) from Phetchaburi Province, western Thailand - Donbundit, Nattasuda; Sumontha, Montri; Suthanthangjai, Maneerat; Suthanthangjai, Winai; Pauwels, Olivier S. G. (Zootaxa, 2024)
We describe Dixonius chotjuckdikuli sp. nov. from Khao Ebid (Mount Ibit), Khao Yoi District, Phetchaburi Province, western Thailand. The new, limestone-dwelling species differs from all currently recognized species of Dixonius by the following combination of morphological characters and pattern: maximal known snout-vent length of 45.6 mm, 18 (rarely 16) longitudinal rows of dorsal tubercles; 31 to 34 paravertebral scales; 18 (rarely 16) longitudinal rows of ventral scales across the abdomen; 20 to 22 interciliary scales; 5 or 6 precloacal pores in males, no pores in females; a marked canthal stripe extending beyond the shoulder; and a blotched dorsal pattern in males, females and juveniles. This description brings the number of Dixonius species to 17, among which seven species are endemic to Thailand.